Palaeontology: Tiny fossils in the animal family tree - Rahman, I (Springer Nature, 2017)
Newly discovered microscopic fossils might shed light on the early evolution of the deuterostomes, the animal group that includes vertebrates. But more work is needed to resolve the fossils' place in the deuterostome tree.